Deformation features of the Higher Himalayan Crystallines in Western Bhutan during exhumation - Carosi, Rodolfo; Montomoli, Chiara; Visonà, Dario (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp. 108